Production of disposable biodegradable cups based on watermelon peel waste modified with zinc oxide nanoparticles and red cabbage extract - Fahime Purghorbani; Sajad Pirsa; Ayoub Fathollahi Qarachoboogh (Applied Food Research)
This study investigates the preparation of disposable biodegradable cups using watermelon peel (WMP) waste, modified with zinc oxide nanoparticles (ZnO) and red cabbage extract (RCE). We analyzed the physicochemical, structural, and biodegradability properties of the resulting cups. Increasing the amounts of RCE and ZnO enhanced the thickness and solubility of the cups. The control sample exhibited higher hardness compared to the composites. Notably, the addition of ZnO reduced moisture content and swelling, while the permeability to water vapor significantly decreased in samples containing both ZnO and RCE. Scanning Electron Microscopy (SEM) revealed cracks and crevices in the composite surfaces. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the chemical structure, and X-ray Diffraction (XRD) analyses indicated a semi-crystalline structure. Thermogravimetric Analysis (TGA) demonstrated improved thermal stability with the addition of nanoparticles and extracts. The cups made from pure WMP displayed substantial antioxidant properties, which were enhanced by RCE and ZnO. While biodegradability increased with ZnO concentration, it decreased with higher RCE levels. This research highlights the potential of WMP, ZnO, and RCE combinations for developing sustainable disposable cups with favorable mechanical properties for commercial applications.